AaEIN3 Mediates the Downregulation of Artemisinin Biosynthesis by Ethylene Signaling Through Promoting Leaf Senescence in Artemisia annua - Tang, Yueli; Li, Ling; Yan, Tingxiang; Fu, Xueqing; Shi, Pu; Shen, Qian; Sun, Xiaofen; Tang, Kexuan (Frontiers in Plant Science, 2018)
Artemisinin is an important drug for malaria treatment, which is exclusively produced in Artemisia annua. It’s important to dissect the regulatory mechanism of artemisinin biosynthesis by diverse plant hormones and transcription factors. Our study shows ethylene, a plant hormone which accelerates flower and leaf senescence and fruit ripening, suppressed the expression of genes encoding three key enzymes ADS, DBR2, CYP71AV1, and a positive regulator AaORA involved in artemisinin biosynthesis. Then we isolated the gene encoding ETHYLENE-INSENSITIVE3 (EIN3), a key transcription factor in ethylene signaling pathway, by screening the transcriptome and genome database from Artemisia annua, named AaEIN3. Overexpressing AaEIN3 suppressed artemisin biosynthesis, while repressing its expression with RNAi enhanced artemisinin biosynthesis in Artemisia annua, indicating AaEIN3 negatively regulates artemisinin biosynthesis. Further study showed the downregulation of artemisinin biosynthesis by ethylene required the mediation of AaEIN3. AaEIN3 could accelerate leaf senescence, and leaf senescence attenuated the expression of ADS, DBR2, CYP71AV1 and AaORA that are involved in artemisinin biosynthesis. Collectively, our study demonstrated a negative correlation between ethylene signaling and artemisinin biosynthesis, which is ascribed to AaEIN3-induced senescence process of leaves. Our work provided novel knowledge on the regulatory network of plant hormones for artemisinin metabolic pathway.